Teacher-Student Interaction in EFL Classrooms through Creative Problem-Solving: An Application of the Initiation-Response-Feedback Model - Aini, Rani Nur; Drajati, Nur Arifah; Putra, Kristian Adi (VELES Voices of English Language Education Society, 2024)
Effective teaching relies heavily on solid communication and meaningful interaction between teachers and students. These elements create an environment where students are more engaged and motivated, leading to better learning outcomes. One way to enhance this interaction is through Creative Problem-Solving (CPS), which incorporates creativity into the teaching process. CPS encourages students to think imaginatively, collaborate, and apply knowledge dynamically, fostering a more engaging and interactive classroom environment. This study aims to investigate how Creative Problem-Solving (CPS) facilitates teacher-student interaction patterns by applying the Initiation-Response-Feedback (IRF) theory in an EFL classroom at a state university in Indonesia. The study involved 46 pre-service teachers, six males and 40 females, all fifth-semester undergraduate students enrolled in the Curriculum and Material Development course. Data collection methods included deep interviews and classroom observations. The research revealed that pre-service teachers faced challenges with CPS projects, especially those involving telecollaboration. However, they valued the lecturer's guidance and feedback, which played a crucial role in helping them overcome these difficulties and complete the tasks. Thus, to maximize the benefits of CPS, lecturers must provide a clear understanding of CPS principles, as it is a relatively new approach for many pre-service teachers. Additionally, encouraging pre-service teachers to seek guidance and actively engage in collaborative activities can enhance their critical thinking and overall learning experience.